DEVONIAN-CARBONIFEROUS MAGMATISM AND METALLOGENY IN THE SOUTH URAL ACCRETIONARY-COLLISIONAL SYSTEM - A. M. Kosarev (Geodinamika i Tektonofizika, 2021)
The oceanic stage in the history of the South Urals completed in the Ordovician – Early Silurian. The Ordovician through Devonian events in the region included the formation of an island arc in the East Ural zone from the Middle Ordovician to Silurian; westward motion of the subduction zone in the Late Silurian – Early Devonian and the origin of a trench along the Main Ural Fault and the Uraltau Uplift; volcanic eruptions and intrusions in the Magnitogorsk island arc system in the Devonian. The Middle-Late Paleozoic geodynamic evolution of uralides and altaides consisted in successive alternation of subduction and collisional settings at the continent-ocean transition. The greatest portion of volcanism in the major Magnitogorsk zone was associated with subduction and correlated in age and patterns of massive sulfide mineralization (VMS) with Early – Middle Devonian ore-forming events in Rudny Altai. Within-plate volcanism at the onset of volcanic cycles records the Early (D1e2) and Middle (D2ef2) Devonian slab break off. The volcanic cycles produced, respectively, the Buribay and Upper Tanalyk complexes with VMS mineralization in the Late Emsian; the Karamalytash complex and its age equivalents in the Late Eifelian – Early Givetian, as well as the lower Ulutau Formation in the Givetian. Slab break off in the Late Devonian – Early Carboniferous obstructed the Magnitogorsk island arc and supported asthenospheric diapirism. A new subduction zone dipping westward and the Aleksandrovka island arc formed in the Late Devonian – Early Carboniferous. The Early Carboniferous collision and another event of obstructed subduction led to a transform margin setting corresponding to postcollisional relative sliding of plates that produced another slab tear. Postcollisional magmatism appears as alkaline gabbro-granitic intrusives with related rich Ti-magnetite mineralization (C1). Transform faulting persisted in the Middle Carboniferous through Permian, when the continent of Eurasia completed its consolidation. The respective metallogenic events included formation of Cu-Ni picritic dolerites (C2–3), as well as large-scale gold and Mo-W deposits in granites (P1–2).